2017
DOI: 10.1136/bmjopen-2017-017309
|View full text |Cite
|
Sign up to set email alerts
|

Association between vomiting in the first trimester and preterm birth: a retrospective birth cohort study in Wuhan, China

Abstract: ObjectiveAlthough vomiting in the first trimester has been reported to be associated with preterm birth (PTB), findings supporting this association remain inconsistent. Our aim was to assess the association between vomiting and PTB, as well as evaluate if the association is modified by pre-pregnancy body mass index (BMI).DesignA retrospective cohort study.SettingWuhan, a central city of China.ParticipantsA total of 317 463 pregnant women who had a live, singleton newborn from 1 January 2010 to 23 May 2016 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 39 publications
3
21
1
Order By: Relevance
“…However, no studies to date have examined the effect of nausea, vomiting or poor appetite during pregnancy on preterm birth in a low-income, rural setting as in this study. (4,23,25,28,29) The present study showed a cumulative incidence of nausea, vomiting or poor appetite of 60.6% during the rst trimester, which is on the lower end of what has been previously reported. (1,5) Previous literature has shown that nausea and vomiting during pregnancy is less likely to be reported among Asian and African populations as compared to Caucasian populations and the cumulative incidence in the current study agrees with previously reported numbers from Bangladesh and Tanzania.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, no studies to date have examined the effect of nausea, vomiting or poor appetite during pregnancy on preterm birth in a low-income, rural setting as in this study. (4,23,25,28,29) The present study showed a cumulative incidence of nausea, vomiting or poor appetite of 60.6% during the rst trimester, which is on the lower end of what has been previously reported. (1,5) Previous literature has shown that nausea and vomiting during pregnancy is less likely to be reported among Asian and African populations as compared to Caucasian populations and the cumulative incidence in the current study agrees with previously reported numbers from Bangladesh and Tanzania.…”
Section: Discussionsupporting
confidence: 57%
“…(12,24) Nausea and vomiting, in particular severe vomiting such as in hyperemesis gravidarum, has been linked to inadequate weight gain and potentially even weight loss. (12,13,16,17,25) If we had information on weight at the start of pregnancy, we might also have been able to detect weight loss and, with that, potentially detect hyperemesis gravidarum in the enrolled women. Future studies should attempt to design data collection so that it allows for pre-pregnancy or early rst trimester BMI and weight to be collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equivocal results around preterm birth have been observed in previous studies, however, no studies to date have examined the effect of NVP during pregnancy on preterm birth in a low-income, rural setting as in this study. (4,17,19,23,24) The present study showed a prevalence of NVP of 60.6% during the first trimester, which is on the lower end of what has been previously reported. (1, 5) Previous literature has shown that NV during pregnancy is less likely to be reported among Asian and African populations as compared to Caucasian populations and the prevalence in the current study agrees with previously reported prevalence rates from Bangladesh and Tanzania.…”
Section: Discussionsupporting
confidence: 50%
“…NV has been associated with lower-than-recommended weight gain in pregnancy, which in turn has been associated with small for gestational age infants (SGA) and prematurity. (9,16,18,19) SGA is considered a measure of intrauterine growth restriction, as genetic differences in birth size are relatively small in healthy pregnancies. (20) The strength of association of NV of pregnancy with SGA, LBW and preterm birth are inconsistent in the literature.…”
Section: Introductionmentioning
confidence: 99%